Analisis Pengaruh Kualitas Layanan, Persepsi Harga, Citra Merek Dan Lokasi Terhadap Keputusan Pembelian: (Studi Pada Konsumen Hotel Ayola Sunrise di Kota Mojokerto) - Yosi Arivianto; Ali Maskur (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the impact of service quality, price perception, brand image, and location on consumer purchasing decisions at Ayola Sunrise Hotel in Mojokerto City. Assessment of service quality in reliability, responsiveness, assurance, empathy, and physical evidence; evaluation of price perception depends on the level of price fairness perceived by consumers; brand image is assessed based on consumer perceptions of the reputation and image of Ayola Sunrise Hotel and location assessment is carried out by considering the accessibility and strategic position of the hotel. This study uses a quantitative methodology with a survey instrument administered to customers and analyzed through multiple linear regression techniques. The findings of this study indicate that Service Quality has a partial and significant influence on Purchasing Decisions; Price Perception shows a significant partial influence on purchasing decisions; Brand Image has a significant partial influence on purchasing decisions; Location shows a significant partial influence on purchasing decisions. Meanwhile, Service Quality, Price Perception, Brand Image, and Location have a significant impact together on purchasing decisions.